Indicadores de vocabulário receptivo de meninas com síndrome de Rett com o uso de equipamento de rastreio ocular - Xavier, Jucineide Silva (2020)
Rett Syndrome (RS) is a condition in which the affected child, almost always female, has severe impairments in motor skills (loss of intentional use of hands, abnormal gait and, sometimes, inability to walk), communicative (lack of speech, in most cases) and cognitive (profound intellectual disability). Studies using eye-tracking technology showed that girls with RS are able to communicate through the eye and that this technology is safe and effective to evaluate their cognitive aspects. However, there are still no reliable information on the receptive language of these girls. This study is the first, which is known, that evaluated the receptive vocabulary of RS girls through the use of eye-tracking equipment and compared the results obtained with the parents' perception of this same ability. 14 girls with RS and 11 girls with typical development participated in this study. The following instruments were used: kerr scale (to describe the atypical girls’ condition), Communication and symbolic behavior scales (CSBS DP) infant-toddler checklist and communicative difficulties questionnaire (to evaluate the parents perception of their daughters communication skills and difficulties), Tobii Pro X3-120 equipment (eye-tracking device) and the peabody picture vocabulary test - PPVT4 (to evaluate receptive vocabulary). The PPVT-4 images were shownin a computer screen, where the eye-tracking equipment was attached, for 5 seconds for familiarization and for another 5 seconds for testing. The girls should look at the image that represented the word they heard. This procedure was repeated 3 times; however, in a random order. According to the parent`s perception, RS girls do not have difficulty understanding, although they have reported difficulties communicating with them, and low societal acceptance. The girls with RS underperformed the typical 3 to 4 years old girls in the eye-tracking assessment. The results indicated that the younger girls and those with less severe condition performed better in the task, in addition, the number of fixations proved to be a good method to measure the performance of this population. Finally, indicators suggest that the more the parents reported that their daughters knew the word, the more chances they had of looking for the right stimulus. Furthermore, there is indication that the girls understood and tried to find the right stimulus during testing, therefore, the need for further studies, with a larger sample.